Anthocyanin and Chlorophyll Content in Flush as Selection Markers on Fine Flavor Cocoa (Theobroma cacao L.) - Indah Anita Sari; Sobir .; Irvan Faizal; Agung Wahyu Susilo; Marcelinus A.S; Adhiwibawa .; R.A.P. Nugroho (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2016)
Level of anthocyanin content in flush is different between fine flavor cocoa and bulk cocoa. This study was aimed to determine the potential of anthocyanin and chlorophyll content in flush as one of the selection indicator for fine flavor cocoa. Flush sampling was carried out at Cocoa Germplasm Collections in Kaliwining Experimental Station, Indonesian Coffee and Cocoa Research Institute, while anthocyanin and chlorophyll analysis was conducted at Laboratory of Ma Chung Research Center for Photosynthetic Pigments, Ma Chung University, Malang.The research utilized a completely randomized design consisted of four genotypes of fine flavor cocoa, namely DR 2, ICCRI 02, DRC 16, PNT 16 and five genotypes of bulk cocoa, namely Sulawesi 1, MCC 01, MCC 02, KW 617 and PA 191.Each treatment was repeated three times. Anthocyanin and chlorophyll content in flush was measured. Anthocyanin analysis was done by destructive methods, while flush color was observed based on Munsell Color Chart for Plant Tissues Data analysis used orthogonal contrast, multivariate and simple correlation. The results showed that there were differences in flush color on fine flavor cocoa and that of bulk cocoa. The flush of the fine flavor cocoa had a tendency towards yellow and that of bulk cocoa had a tendency toward red with different levels of variation among genotypes. The analysis results of chlorophyll content in flush showed that chlorophyll content of fine flavor cocoa was higher than bulk cocoa with a range of 2376-3692 µmol/L for fine flavor cocoa and 1567-2628 µmol/L for bulk cocoa. On the contrary, anthocyanin content in fine flavor cocoa was lower than bulk cocoa with a range of 3.82-5.72 µmol/L for fine flavor cocoa and 6.01-11.88 µmol/L for bulk cocoa. The analysis results of orthogonal contrasts showed that chlorophyll content value was more stable than anthocyanin. There was negative relationship between anthocyanin and chlorophyll in flush with the regression Y = -221,1X + 3935 with a value of correlation r = -0.50. The anthocyanin and chlorophyll content in flush had a potential to be used as selection markers for fine flavor cocoa hybrid